Identification: the missing link within the rhetoric of social movements - Christiansen, Jordan (Kansas State University, 2014)
The term and concept of identification is a familiar one. The modern communication scholar’s knowledge of the term identification is drawn more directly from the works of Kenneth Burke. In 1950 Kenneth Burke released his book “A Rhetoric of Motives” and from this Burke outlined his concept of identification. To Burke, identification is a rhetorical process that leads to persuasion, and the identification process encompasses all the traditional forms of rhetoric as a category of tools to establish identification within rhetorical discourse (Burke, 1950; Day, 1960). The concept of identification has been applied generously as the field of rhetoric has progressed. However, a minimal amount of research connecting identification and the rhetoric of social movements has been conducted. This is a problem, because social movements rely heavily on persuasion and influence to garner audience support, so a deeper investigation into identification and social movement rhetoric is warranted. In recent years the marriage equality movement has seen a rapid amount of success in establish same-sex marriage in a variety of states. What has changed that has allowed these movements to reach so much success so quickly? I believe the answer to this question lies in the rhetoric of these movements and their use of identification. This thesis asks an overarching question; “Does identification help to explain the success of a social movement?” Applying Burke’s concept of identification to two marriage equality movements, Minnesotans United for All Families and Fair Wisconsin, this thesis seeks to determine the role identification plays in a social movements success or failure. What this thesis finds is that identification is a vital component in determining a social movements overall success. Identification is a two-step process, where first identification strategies need to be present within a social movement’s rhetoric. For identification strategies to be effective not only must the strategies be present but also the audience must link these strategies with their subconscious and thereby include the movement as a part of his or her identity. In conducting this thesis critical implications are drawn in relation to identification theory, organizational recruitment and maintenance, as well as community building and engagement.
Keywords: Identification; Burke; Social Movements; Rhetoric; Persuasion; Communication (0459)